Are Schools Different? Wellbeing and Commitment among Staff in Schools and Elsewhere - Alex Bryson; Lucy Stokes; David Wilkinson (Institute of Labor Economics (IZA), 2018)
Using nationally representative linked employer-employee data for Britain in 2004 and 2011 we find school staff are more satisfied and more contented with their jobs than "like" employees in other workplaces. The differentials are largely accounted for by the occupations school employees undertake and perceptions of job quality. School employees are also more committed to their organization than non-school employees, a difference that remains large and statistically significant having conditioned on job quality, human resource management practices (HRM), managerial style and other features of employees' working environment. Using panel data for workplaces and their employees observed in 2004 and 2011 we find increases in organizational commitment are linked to improvements in workplace performance in schools, but not in other workplaces.
Keywords: I21; 330; schools; teachers; job satisfaction; job contentment; organizational commitment; school performance; human resource management; managerial style